Different changes of bacterial diversity and soil metabolites in tea plants-legume intercropping systems - Wang, Shuangshuang; Zhang, Xiaojia; Li, Xiaojiang; Shen, Jiazhi; Sun, Litao; Zaman, Shah; Wang, Yu; Ding, Zhaotang (Frontiers in Plant Science, 2023)
As an essential agroforestry, intercropping legumes can improve the physical, chemical, and biological fertility of the soil in tea plantations. However, the effects of intercropping different legume species on soil properties, microbial communities, and metabolites remain elusive. In this study, the 0-20 cm and 20-40 cm soils of three planting patterns (T1: tea plants/mung bean intercropping, T2: tea plants/adzuki bean intercropping, T3: tea plants/mung bean and adzuki bean intercropping) were sampled to explore the diversity of the microbial community and soil metabolites. The findings showed that, as compared to monocropping, intercropping systems had greater concentrations of organic matter (OM) and dissolved organic carbon (DOC). Notably, pH values were significantly lower, and soil nutrients increased in intercropping systems compared with monoculture in 20-40 cm soils, especially in T3. In addition, intercropping resulted in an increased relative abundance of Proteobacteria but a decreased relative abundance of Actinobacteria. 4-methyl-Tetradecane, acetamide, and diethyl carbamic acid were key metabolites mediating the root–microbe interactions, especially in tea plants/adzuki intercropping and tea plants/mung bean, adzuki bean mixed intercropping soils. Co-occurrence network analysis showed that arabinofuranose, abundant in tea plants and adzuki bean intercropping soils, showed the most remarkable correlation with the soil microbial taxa. Our findings demonstrate that intercropping with adzuki beans is better at enhancing the diversity of soil microorganisms and soil metabolites and is a more economical strategy than other tea plants/legume intercropping systems.